New combinations in the genus Didymoplexis (Orchidaceae; Epidendroideae; Gastrodieae), with a new variety of D. siamensis from Amami-Oshima Island, Japan - Suetsugu, Kenji; Hsu, Tian-Chuan (Phytotaxa, 2019)
The mycoheterotrophic orchid genera Didymoplexiella Garay (1955: 33) and Didymoplexis Griffith (1844: 383) include seven and ca. 20 species, respectively (Averyanov 2011, Hu et al. 2014, Tsukaya et al. 2014, Suetsugu et al. 2017). Didymoplexiella is similar in both habit and floral appearance to Didymoplexis, with which it was considered congeneric by some earlier authors (Smith 1920, Holttum 1953). However, modern taxonomists generally agreed that Didymoplexiella species can be distinguished from Didymoplexis species by the presence of a pair of long recurved stelidia on the tip of the column and the absence of a distinct column foot (Garay 1954, Seidenfaden 1978, Seidenfaden & Wood 1992, Su 2000, Comber 2001, Jin et al. 2004, Pridgeon et al. 2005, Tsukaya et al. 2005, 2014, Chen et al. 2009, Rojchana-Umpawan et al. 2014, Yokota et al. 2016).